ANALISIS PERBANDINGAN KINERJA REKSA DANA PT DANAREKSA INVESTMENT MANAGEMENT DENGAN PT MANDIRI MANAJEMEN INVESTASI SELAMA PERIODE KRISIS EROPA 2011-2012 BERDASARKAN RISK ADJUSTED RETURN (SHARPS, TREYNOR, DAN JENSEN ALPHA RATIO) - , Nurisdipta Nusaputra, Prof. Dr. Marwan Asri S., MBA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study was to analyze and compare several mutual funds issued by the two government companies engaged in capital market, namely PT. Danareksa Investment Management and PT. Mandiri Investment Management during a period of crisis in Euro-Zone. The selected mutual funds are divided among the three kinds of mutual funds are equity funds, mixed funds, and fixed income funds for comparative analysis based on risk adjusted return. In this study, the authors calculate the performance of each mutual fund issued by PT. Danareksa Investment Management and PT. Mandiri Investment Management (Danareksa Mawar, Danareksa Anggrek, Danareksa Gebyar Indonesia II, Mandiri Investa Atraktif, Mandiri Investa Aktif, Mandiri Investa Dana Utama) during the period of crisis in Euro-Zone (year 2011 until the year 2012) by using the risk-adjusted performance through the Sharpe ratio, Treynor ratio, and the ratio of Differential Return. Since this method calculates between return and risk, the authors need a data of a return from selected mutual fund products since the beginning of September 2011 until the end of July 2012 from net asset value of mutual funds data. The results of this study will show that during the crisis period, an indication of high returns from a mutual fund may not necessarily result in positive returns after the risk free rate. In addition, a mutual fund may not necessarily have a low risk as reflected in the value of the return variability and volatility of the supermarket. As well as the return of mutual funds still can not beat the performance observed marketnya (index) during bearish. The results of this comparative analysis also shows mutual fund products which are superior when compared to similar products, in addition, this study shows the performance of mutual funds between PT. Danareksa Investment Management and PT. Mandiri Investment Management cumulatively to determine the investment management company whose performance is better during the Euro-Zone crisis.